Drug–drug and drug–food interactions in an infant with early‐onset SCN2A epilepsy treated with carbamazepine, phenytoin and a ketogenic diet. Issue 3 (13th August 2020) - Welzel, Tatjana; Ziesenitz, Victoria C.; Weber, Peter; Datta, Alexandre N.; van den Anker, Johannes N.; Gotta, Verena
Abstract : Sodium channel 2 subunit α ( SCN2A ) mutations cause difficult‐to‐treat early‐onset epilepsy. Effective treatment includes high‐dose phenytoin or carbamazepine ± ketogenic diet (KD). We describe an infant with early‐onset SCN2A ‐epilepsy with subtherapeutic carbamazepine concentration during transition from phenytoin treatment to avoid long‐term neurotoxicity. The transition from high‐dose phenytoin (20 mg kg −1 d −1, concentration: ≥20 mg/L) with KD, to carbamazepine (50–75 mg kg −1 d −1, concentration: 9–12 mg/L) lasted 85 days, which we suspected was due to significant drug–drug and/or drug–food interactions. Model‐based analysis of carbamazepine pharmacokinetics quantified significant time‐ and dose‐dependent phenytoin‐mediated CYP3A4 induction and carbamazepine concentration‐dependent auto‐induction (apparent clearance increased up to 2.5/3‐fold). Lower carbamazepine concentrations under KD were modelled as decreased relative bioavailability (44%), potentially related to decreased fraction absorbed (unexpected for this lipophilic drug), increased intestinal/hepatic metabolism and/or decreased protein‐binding with KD. This suggests importance of carbamazepine‐concentration monitoring during KD‐introduction/removal and necessity of high carbamazepine doses to achieve therapeutic concentrations, especially in infants treated with high‐dose phenytoin.